2020
DOI: 10.1016/j.heares.2020.107910
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band ripple glide direction discrimination and its relationship to frequency selectivity estimated using psychophysical tuning curves

Abstract: Discrimination of narrowband spectral ripples 1 1 Narrow-band ripple glide direction discrimination and its relationship to frequency 2 selectivity estimated using psychophysical tuning curves 3 4 Vijaya Kumar Narne a) 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Impaired spectral modulation sensitivity with a cochlear implant is a likely result of its band-pass filtering mechanism that limits the spectral information to a set number of spectral bands. Henry et al (2005), Berenstein et al (2008) and Narne et al (2020) all found lower spectral ripple modulation thresholds for cochlear-implant users compared to normal-hearing listeners, roughly corresponding to the increased reaction times in our study. Spectral modulation thresholds in hearing-impaired listeners have been reported to be 5–10 dB worse than for normal hearing (Davies-Venn et al, 2015; Summers & Leek, 1994), which may agree with the longer reaction times of our hearing-aid simulation compared to normal hearing.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Impaired spectral modulation sensitivity with a cochlear implant is a likely result of its band-pass filtering mechanism that limits the spectral information to a set number of spectral bands. Henry et al (2005), Berenstein et al (2008) and Narne et al (2020) all found lower spectral ripple modulation thresholds for cochlear-implant users compared to normal-hearing listeners, roughly corresponding to the increased reaction times in our study. Spectral modulation thresholds in hearing-impaired listeners have been reported to be 5–10 dB worse than for normal hearing (Davies-Venn et al, 2015; Summers & Leek, 1994), which may agree with the longer reaction times of our hearing-aid simulation compared to normal hearing.…”
Section: Discussionsupporting
confidence: 73%
“…Narne et al (2016, 2018, 2020) have studied spectral resolution by means of a spectral-ripple or a moving-ripple test. They found thresholds around 5 to 6 cycles/octave for normal-hearing listeners in optimal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, as a cautionary note, we point out that the question of spectral/temporal separability must be addressed with additional experiments specifically targeting this issue, because the engagement (or lack thereof) of relevant mechanisms likely depends on task demands. For example, a model with separable spectral and temporal processes, or simply based on the variance of modulations across peripheral channels (Chabot-Leclerc et al., 2014), would not explain why listeners are able to discriminate upward versus downward STMs (Archer-Boyd et al., 2018; Denham, 2005; Narne et al., 2020), as it would return the same output for the two directions. Particular attention should be devoted to this question in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, as pointed out by the authors (see Miller et al, 2018), several distinct mechanisms might be conflated by these measurements: broader cochlear filters due to hearing loss as well as deficits related to other processes (that were not engaged with pure tones), such as temporal fine structure (TFS) processing. In relation to the former aspect, some recent studies go as far as suggesting that upward/downward STM discrimination thresholds could serve as a proxy measure for auditory filter bandwidth (BW; Narne et al, 2019Narne et al, , 2020. In addition, it is important to note that these studies have examined factors that limit the ability of HI listeners to detect modulations at threshold, but these factors may differ from those recruited when extracting suprathreshold STMs from modulation noise, such as in the context of Oetjen and Verhey's (2015) masking paradigm.…”
mentioning
confidence: 99%
“…If high ripple-density resolution occurs due to the discrimination of combination-product spectra, such masking should reduce the resolution characteristic of discrimination between rippled and nonrippled signals to that characteristic of discrimination between two rippled signals. A masking pink noise in the frequency band of expected low-frequency combination products was used by Narne et al. (2020) , although comparison of masking effects depending on discrimination task was not made in that study.…”
Section: Combination Products As Possible Mechanisms Of Ripple Pattern Resolutionmentioning
confidence: 99%